Atlantic Multidecadal Variability in a model with an improved North Atlantic Current - Annika Drews; Richard J. Greatbatch (Geophysical Research Letters)
Abstract We examine the simulated Atlantic Multidecadal Variability (AMV) in a model that includes a correction for a long‐standing problem with climate models, namely, the misplacement of the North Atlantic Current. The corrected model shows that in the warm AMV phase, heat is lost by the ocean in the northwestern part of the basin and gained by the ocean to the east, suggesting an advective transfer of heat by the midlatitude westerlies. The basin‐wide response is consistent with a role for cloud feedback and is in broad agreement with estimates from observations but is poorly represented in the uncorrected model. The corrected model is then used to show that the ocean/atmosphere heat transfer is influenced by low‐frequency variability in the overlying atmosphere. We also argue that changing ocean heat transport is an essential feature of our results.